Short Communication: Ethnozoology – The perception of Tobelo Dalam tribal community in Saolat Village, East Halmahera, Indonesia towards cuscus (Phalangeridae) - ELIZABETH NOVI KUSUMANINGRUM; JATNA SUPRIATNA; ABINAWANTO ABINAWANTO; ANOM BOWOLAKSONO (Society for Indonesian Biodiversity, 2018)
Kusumaningrum EN, Supriatna J, Abinawanto, Bowolaksono A. 2018. Short Communication: Ethnozoology – The perception of Tobelo Dalam tribal community in Saolat Village, East Halmahera, Indonesia towards cuscus (Phalangeridae). Biodiversitas 19: 2140-2146. The complexity of the hard lives of Tobelo Dalam tribal community who live in Saolat village, district South Wasile provokes the high activity of animal poaching in Aketajawe-Lolobata National Park (TNAL) including cuscus hunting for both sale and consumption purposes. The study aimed to describe the traditional knowledge of Tobelo Dalam people in Saolat village in applying the systems of utilization and local conservation knowledge towards cuscus. This study was analyzed by the qualitative method with explorative survey technique, interview, and completing questionnaires. This study used 4 key informants (3 males, 1 female) and 50 adult respondents (25 males and 25 females). The results showed that the average percentage of traditional knowledge owned by males and females were 69.1% and 30.9 %, respectively, so the males had an advantage of knowledge around 38.3 % than females in addressing the traditional knowledge of cuscus. The community of Tobelo Dalam tribe hunts cuscus for four different purposes, i.e., for traditional ceremonies, traditional medicine, cuisine, and sell it for more income to support the economy of family.